Peningkatan Kemampuan Paduan Suara di Kelas VII2 SMP Negeri 42 Padang Menggunakan Metode Latihan (Drill) - Putri Regina Aprillia; Olan Yogha Pratama (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The problems in this research are inappropriate sound production techniques, such as still using chest breathing when singing, inappropriate intonation, unclear articulation, and inappropriate phrasing or sentence breaks in songs. This research aims to determine and describe efforts to improve choir abilities in class VII2 of SMP Negeri 42 Padang using the drill method. This research is classroom action research using the Kemmis and Mc Taggart model which was carried out in two cycles, each cycle consisting of four stages, namely: a) planning, b) implementation, c) observation and d) reflection. The results of this research indicate that the use of the drill method in the choir learning process in the choir team in class VII2 of SMP Negeri 42 Padang can improve students' ability to sing in a choir. This can be proven by obtaining an average score from the singing evaluation results. The average value obtained was pre-cycle 65%, cycle I 70.23%, and cycle II 75.71%.